A.
To solve, you need to get the variable by itself.
Order of operations:
Square root both sides.
(x-5)= plus/minus root 3, as 3 is not a perfect square.
Now you need to add 5 to both sides to get it to disappear on the side with the x.
x=root3 +or - 5, which can be rearranged so that 5 is the first term.
Answer:
(f+g)(x) = -3x+5
Step-by-step explanation:
f(x)=x+8 and g(x)=-4x-3
(f+g)(x) = f(x) + g(x)
= x+8+-4x-3
= -3x+5
Answer:
Angle WZY=31degrees
Step-by-step explanation:
5x+11=8x-1
11+1=8x-5x
12=3x
X=12/3
X=4
Substitute x=4 in 5x+11
5(4)+11=31
Answer:
- ![\frac{8}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B7%7D)
Step-by-step explanation:
Given
← cancel sec x on numerator/ denominator
= ![\frac{8}{-7}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B-7%7D)
= - ![\frac{8}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B7%7D)
Answer:
f(x) = -(x-4)^2 + 5
Step-by-step explanation:
The function
is a quadratic function. Its graph looks like a parabola. The graph has a vertex of (4,5) and opens up downward.
Proving that
for all x:
![x^2 \ge 0 \Rightarrow (x-4)^2 \ge 0 \Rightarrow -(x-4)^2 \le 0 \Rightarrow -(x-4)^2 + 5 \le 5.](https://tex.z-dn.net/?f=x%5E2%20%5Cge%200%20%5CRightarrow%20%28x-4%29%5E2%20%5Cge%200%20%5CRightarrow%20-%28x-4%29%5E2%20%5Cle%200%20%5CRightarrow%20-%28x-4%29%5E2%20%2B%205%20%5Cle%205.)